Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the given system of equations using the substitution method, follow these steps:
Given the system of equations:
[tex]\[ \begin{array}{l} 3x + 2y = 13 \quad \text{(Equation 1)} \\ y = x - 1 \quad \text{(Equation 2)} \end{array} \][/tex]
1. Substitute the expression for \( y \) from Equation 2 into Equation 1.
From Equation 2, we know:
[tex]\[ y = x - 1 \][/tex]
Substitute \( y = x - 1 \) into Equation 1:
[tex]\[ 3x + 2(x - 1) = 13 \][/tex]
2. Simplify and solve for \( x \):
[tex]\[ 3x + 2x - 2 = 13 \][/tex]
Combine like terms:
[tex]\[ 5x - 2 = 13 \][/tex]
Add 2 to both sides of the equation:
[tex]\[ 5x = 15 \][/tex]
Divide both sides by 5:
[tex]\[ x = 3 \][/tex]
3. Substitute \( x = 3 \) back into Equation 2 to find \( y \):
[tex]\[ y = x - 1 \][/tex]
[tex]\[ y = 3 - 1 \][/tex]
[tex]\[ y = 2 \][/tex]
4. Verify the solution by substituting \( x = 3 \) and \( y = 2 \) into both original equations:
Check Equation 1:
[tex]\[ 3x + 2y = 13 \][/tex]
[tex]\[ 3(3) + 2(2) = 13 \][/tex]
[tex]\[ 9 + 4 = 13 \][/tex]
Check Equation 2:
[tex]\[ y = x - 1 \][/tex]
[tex]\[ 2 = 3 - 1 \][/tex]
Both equations are satisfied with \( x = 3 \) and \( y = 2 \).
Therefore, the solution to the system of equations is:
[tex]\[ \boxed{(3, 2)} \][/tex]
The correct answer is:
[tex]\[ \text{B. } (3, 2) \][/tex]
Given the system of equations:
[tex]\[ \begin{array}{l} 3x + 2y = 13 \quad \text{(Equation 1)} \\ y = x - 1 \quad \text{(Equation 2)} \end{array} \][/tex]
1. Substitute the expression for \( y \) from Equation 2 into Equation 1.
From Equation 2, we know:
[tex]\[ y = x - 1 \][/tex]
Substitute \( y = x - 1 \) into Equation 1:
[tex]\[ 3x + 2(x - 1) = 13 \][/tex]
2. Simplify and solve for \( x \):
[tex]\[ 3x + 2x - 2 = 13 \][/tex]
Combine like terms:
[tex]\[ 5x - 2 = 13 \][/tex]
Add 2 to both sides of the equation:
[tex]\[ 5x = 15 \][/tex]
Divide both sides by 5:
[tex]\[ x = 3 \][/tex]
3. Substitute \( x = 3 \) back into Equation 2 to find \( y \):
[tex]\[ y = x - 1 \][/tex]
[tex]\[ y = 3 - 1 \][/tex]
[tex]\[ y = 2 \][/tex]
4. Verify the solution by substituting \( x = 3 \) and \( y = 2 \) into both original equations:
Check Equation 1:
[tex]\[ 3x + 2y = 13 \][/tex]
[tex]\[ 3(3) + 2(2) = 13 \][/tex]
[tex]\[ 9 + 4 = 13 \][/tex]
Check Equation 2:
[tex]\[ y = x - 1 \][/tex]
[tex]\[ 2 = 3 - 1 \][/tex]
Both equations are satisfied with \( x = 3 \) and \( y = 2 \).
Therefore, the solution to the system of equations is:
[tex]\[ \boxed{(3, 2)} \][/tex]
The correct answer is:
[tex]\[ \text{B. } (3, 2) \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.